Correlation Between Muscle Structures and Electrical Properties of the Tibialis Anterior in Subacute Stroke Survivors: A Pilot Study - Hu, Chengpeng; Hu, Huijing; Mai, Xiaopeng; Lo, Wai Leung Ambrose; Li, Le (Frontiers in Neuroscience, 2019)
Electrical impedance myography (EIM) is a noninvasive diagnostic tool that assesses the muscle inherent properties, whereas ultrasonography can assess the alteration in muscle architecture. This study aimed to combine EIM with ultrasonography to assess the changes of the tibialis anterior (TA) muscle properties during passive plantar/dorsiflexion in stroke survivors. Fifteen patients with subacute stroke were recruited. The muscle structures were simultaneously assessed by EIM and ultrasonography at five different extension angles (-10°, 0°,10°,20°, and 30°) of the ankle joint. The EIM parameters measured were resistance (R), reactance(X), and phase angle (θ). The parameters recorded by ultrasonography were pennation angle (PA), muscle thickness (MT), and fascicle length (FL). Two-way repeated ANOVA was performed to compare the differences between the affected and the unaffected side as well as the parameters changed with joint angle. Linear correlation analysis was conducted to assess the association between muscle parameters and clinical scores. The results showed that as the ankle was passively plantarflexed, the θ (P = 0.003) and PA (P< 0.001) values decreased, and the X(P<0.001), R (P<0.001),and FL(P< 0.001) values increased. Significant correlations were found between the FL and R values (r = 0.615, P = 0.015), MT and R values (r = 0.522, P = 0.046), and FL and θ values(r = 0.561, P = 0.03), as well as between the PA and the Fugl-Meyer Lower Extremity score(r = 0.615, P = 0.015), the R and the MAS score (r = 0.58, P = 0.023), and the PA and the MMT score (r = -0.575, P = 0.025). This study demonstrated a correlation between the EIM and the ultrasonography parameters at different joint angles. Therefore, both methods could jointly be applied in patients with stroke to detect changes in the muscle inherent properties and muscle architecture. This could assist clinicians to quantitatively evaluate the muscle condition in people with subacute stroke.